Dampak Pola Asuh Orang Tua Tunggal (Ibu) Terhadap Perkembangan Anak - Nurul Atikah; Siti Aisyah; Dwi Putri Lestari; Hidayani Syam (JOURNAL SAINS STUDENT RESEARCH, 2025)
Family Psychodynamics is a counseling approach that focuses on understanding the psychological dynamics in family relationships, especially conflicts and tensions arising from past experiences, with the aim of understanding relationship patterns, resolving conflicts, and improving relationships. This research uses a literature study approach. Literature study is a required activity in research, which aims to develop theoretical and practical aspects. The results of the study show that the three family counseling approaches can be applied in the Indonesian context to help families overcome problems and improve harmony. For example, family psychodynamics can help Indonesian families overcome conflicts arising from past experiences, such as rapid social and cultural changes. Behavioral counseling can help Indonesian families overcome behavioral problems in children and adolescents, such as juvenile delinquency. Structural family approach can help Indonesian families understand and overcome problems related to the roles and functions of family members in the context of Indonesian culture and tradition.